Digital breast tomosynthesis: Dose and image quality assessment. (January 2017) - Maldera, A.; De Marco, P.; Colombo, P.E.; Origgi, D.; Torresin, A.
Highlights: Comparison among dose and image quality of four DBT systems is described. Systems performance has been related with the different constructive choices. Physical characterization of a GE system is included. Reconstruction and post processing algorithms deeply affect image quality. Abstract: The aim of this work was to evaluate how different acquisition geometries and reconstruction parameters affect the performance of four digital breast tomosynthesis (DBT) systems (Senographe Essential – GE, Mammomat Inspiration – Siemens, Selenia Dimensions – Hologic and Amulet Innovality – Fujifilm) on the basis of a physical characterization. Average Glandular Dose (AGD) and image quality parameters such as in-plane/in-depth resolution, signal difference to noise ratio (SDNR) and artefact spread function (ASF) were examined. Measured AGD values resulted below EUREF limits for 2D imaging. A large variability was recorded among the investigated systems: the mean dose ratio DBT/2D ranged between 1.1 and 1.9. In-plane resolution was in the range: 2.2 mm −1 –3.8 mm −1 in chest wall-nipple direction. A worse resolution was found for all devices in tube travel direction. In-depth resolution improved with increasing scan angle but was also affected by the choice of reconstruction and post-processing algorithms. The highest z -resolution was provided by Siemens (50°, FWHM = 2.3 mm) followed by GE (25°, FWHM = 2.8 mm), while the Fujifilm HR showed the lowest one, despite its wide scan angle (40°, FWHM = 4.1 mm). The ASF was dependent on scan angle: smaller range systems showed wider ASF curves; however a clear relationship was not found between scan angle and ASF, due to the different post processing and reconstruction algorithms. SDNR analysis, performed on Fujifilm system, demonstrated that pixel binning improves detectability for a fixed dose/projection. In conclusion, we provide a performance comparison among four DBT systems under a clinical acquisition mode.